Kriza univerziteta u Bosni i Hercegovini / The Crisis of Universities in Bosnia and Herzegovina - Islamović, Elvira (Pregled: časopis za društvena pitanja / Periodical for social issues, 2022)
The problems of modern societies affect all parts of educational systems, and the particular impact on higher education. Given many issues, problems and challenges higher education is facing nowadays, the paper discusses the problems of the current and deeper crisis of higher education and gives an overview of different critical views on the role of university. In this thematic context, the most important crises of the higher education system in Bosnia and Herzegovina are being considered. For sociological theory of education, it is crucial to study the social factors and the influence of the social environment on education. Thus, the problems within the higher education sphere are viewed through the prism of the political, economic, sociocultural and moral grounds of the Bosnian society.